Degradation of aflatoxins in weakly alkaline conditions - Sandlin, Natalie; Lee, Jiu; Zaccaria, Marco; Domin, Marek; Momeni, Babak (Frontiers in Sustainable Food Systems, 2025)
Aflatoxins (AFs) are fungal metabolites that ubiquitously contaminate many common food crops and contribute to major foodborne diseases in humans and animals. Known chemical strategies have used strong acids and bases to remove contaminating AF, but these methods often lead to undesired ecological waste issues downstream. In this study, the application of weaker acidic and alkaline conditions to removes two types of AFs, AFB1 and AFG2, is investigated. The results showed that an environment buffered at a pH of 9 reduced AFB1 and AFG2 by more than 50 and 95%, respectively, within 24 h, while acidic conditions did not influence AF levels. The AF degradation was shown to occur through lactone ring opening, a known cause of AF toxicity. Further analysis also provided a putative structure of the AFG2 degradation byproduct. The results confirmed that incubation at a pH of 9 reduced the genotoxicity of AFB1 and found that it was a successful strategy for removing both AFs from artificially contaminated cornmeal. The findings indicated that a weakly alkaline environment had the potential to adequately detoxify AF-contaminated food or feed without the need to apply stronger or harsher basic conditions.